Thiol redox biochemistry: Insights from computer simulations - Zeida Camacho, Ari Fernando (2014)
Thiol redox chemical reactions play a key role in a variety of physiological processes, mainly due to the presence of low-molecular-weight thiols and cysteine residues in proteins involved in catalysis and regulation. Specifically, the subtle sensitivity of thiol reactivity to the environment makes the use of simulation techniques extremely valuable for obtaining microscopic insights. In this work we review the application of classical and quantum-mechanical atomistic simulation tools to the investigation of selected relevant issues in thiol redox biochemistry, such as investigations on (1) the protonation state of cysteine in protein, (2) two-electron oxidation of thiols by hydroperoxides, chloramines, and hypochlorous acid, (3) mechanistic and kinetics aspects of the de novo formation of disulfide bonds and thiol-disulfide exchange, (4) formation of sulfenamides, (5) formation of nitrosothiols and transnitrosation reactions, and (6) one-electron oxidation pathways.